Dr. Glayse June Sasaki Acacio Favarin — Deep Plane Facelift — Criciúma - Sasaki Acacio Favarin, Glayse June (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Glayse June Sasaki Acacio Favarin, practicing in Criciúma, Brazil. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003176; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; brazil; criciúma